CSP01, a Novel Superabsorbent Hydrogel, Reduces Colonic Transit Time in Patients With Chronic Idiopathic Constipation in a Randomized, Double-blind, Controlled Pilot Clinical Trial - Staller, Kyle; Barshop, Kenneth; Vélez, Christopher; Bailey, Abbey; Locascio, Joseph J; Chiquette, Elaine; Kuo, Braden (Journal of neurogastroenterology and motility, 2020)
CSP01 is a novel superabsorbent hydrogel that absorbs gastrointestinal fluids and maintains high viscoelastic properties into the colon, where these fluids are released.Background/AimsCSP01 is a novel superabsorbent hydrogel that absorbs gastrointestinal fluids and maintains high viscoelastic properties into the colon, where these fluids are released.We conducted a single-center, randomized, double-blind, parallel-group, placebo-controlled pilot study comparing change in colonic transit time (CTT) among patients with chronic idiopathic constipation (CIC) and irritable bowel syndrome with constipation (IBS-C) treated for 21 days with either CSP01 hydrogel, active control (carboxymethylcellulose [CMC]) or placebo. CTT was measured using wireless motility capsule transit testing at pre-treatment and end-of-treatment. The primary endpoint was change in CTT.MethodsWe conducted a single-center, randomized, double-blind, parallel-group, placebo-controlled pilot study comparing change in colonic transit time (CTT) among patients with chronic idiopathic constipation (CIC) and irritable bowel syndrome with constipation (IBS-C) treated for 21 days with either CSP01 hydrogel, active control (carboxymethylcellulose [CMC]) or placebo. CTT was measured using wireless motility capsule transit testing at pre-treatment and end-of-treatment. The primary endpoint was change in CTT.Forty subjects (20 CSP01, 11 CMC, 9 placebo) were enrolled and 38 completed the study. There was no significant change in mean CTT by treatment group (P = 0.297). In the placebo group, CTT increased by 15.3 minutes between baseline and end of treatment, increased by 366.4 minutes for CMC, and decreased by 727.4 minutes for CSP01. In post hoc analyses among those with CIC, mean CTT decreased by 1079 minutes for CSP01 (P = 0.025 compared to placebo), 919 minutes for CMC (P = 0.117 compared to placebo) and increased by 1113 minutes for placebo. Among patients with IBS-C, there was no significant difference in change in CTT for any treatment group. One subject in the CSP01 arm developed back pain attributed to constipation and withdrew without a second CTT measurement; there were no other adverse events.ResultsForty subjects (20 CSP01, 11 CMC, 9 placebo) were enrolled and 38 completed the study. There was no significant change in mean CTT by treatment group (P = 0.297). In the placebo group, CTT increased by 15.3 minutes between baseline and end of treatment, increased by 366.4 minutes for CMC, and decreased by 727.4 minutes for CSP01. In post hoc analyses among those with CIC, mean CTT decreased by 1079 minutes for CSP01 (P = 0.025 compared to placebo), 919 minutes for CMC (P = 0.117 compared to placebo) and increased by 1113 minutes for placebo. Among patients with IBS-C, there was no significant difference in change in CTT for any treatment group. One subject in the CSP01 arm developed back pain attributed to constipation and withdrew without a second CTT measurement; there were no other adverse events.CSP01 significantly decreased CTT compared to placebo among patients with CIC, but not in patients with IBS-C.ConclusionCSP01 significantly decreased CTT compared to placebo among patients with CIC, but not in patients with IBS-C.